Contract of service or contract for service: with special reference to the status of graduate research assistants in employment law - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2010)
Nordi has just embarked on his PhD at University Timuran. To earn some good experience and extra income to fund his studies, he sought to do research work as a research assistant for Professor Grouch who was a project leader at the same university. As a research assistant, he was told that he would be paid RM800 for 60 hours of his time, that was spread over a period of one month. He was to search for material, data and carry out sampling as instructed by the Professor. He was also informed that his service would end upon the completion of the task. Further, he could be terminated at anytime if his performance did not meet the mark or if further funding for the research project could not be obtained. On one of his assignments for the Professor and while he was on the way to the National Archives to search for some documents, he lost control of his motorbike and rammed into a tree causing him back injuries. He would like to seek compensation on the basis that he was an employee of Professor Grouch and University Timuran and that he had met with the accident in the course of carrying out the research work for the Professor. The question arises whether he is an employee under a contract of service. If it is found in the affirmative, he would be subject to the various employment statutes providing compensation for work related injuries. This article will therefore, discuss the status of a research officer in employment law.